Advanced Intelligent Computing 7th International Conference, ICIC 2011, Zhengzhou, China, August 11-14, 2011. Revised Selected Papers - Huang, De-Shuang; Gan, Yong; Bevilacqua, Vitoantonio; Figueroa, Juan Carlos (Theoretical Computer Science and General Issues,, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the 7th International Conference on Intelligent Computing, ICIC 2011, held in Zhengzhou, China, in August 2011. The 94 revised full papers presented were carefully reviewed and selected from 832 submissions. The papers are organized in topical sections on neural networks; machine learning theory and methods; fuzzy theory and models; fuzzy systems and soft computing; evolutionary learning & genetic algorithms; swarm intelligence and optimization; intelligent computing in computer vision; intelligent computing in image processing; biometrics with applications to individual security/forensic sciences; intelligent image/document retrievals; natural language processing and computational linguistics; intelligent data fusion and information security; intelligent computing in pattern recognition; intelligent agent and web applications; intelligent computing in scheduling; intelligent control and automation.